Asset accumulation among low-income rural families: Assessing financial capital as a component of community capitals. Issue 2 (15th March 2018) - Meikle, Paulette; Green-Pimentel, Leslie; Liew, Hui
Abstract: Using data from a 2012–2013 empirical study, this article examines financial practices and attitudes toward accumulation of assets among low-income rural families in a county in Mississippi. It dissects "asset accumulation" as an often-ignored facet of the financial component of the Community Capitals Framework. The analysis also examines financial capital creation strategies used by local institutions. The article presents a new theoretical framework for understanding and predicting asset accumulation processes among low-income rural families and resulting community progress. Findings show asset accumulation among low-income rural women and families is hindered by a number of individual and institutional factors. However, a culture of fiscal household responsibility and asset accumulation can be created among women and low-income families. When this occurs, community financial capital as a multiplier effect can be anticipated, which will temporally increase other forms of community capital and progress community.